Peran Folklore Dalam Mendukung Pelestarian Lingkungan Di Pulau Pisang - Ricat Rawanda; Gunardi Djoko Winarno; Indra Gumay Febryano; Sugeng P. Harianto (Universitas Bangka Belitung, 2020)
Conservation activities in conserving environment have been packaged in the form of folklore. This cultural activity has developed in people's lives, but not many have discussed the role of folklore. The research objective is to determine the role of folklore in supporting the preservation of environment in small island. Data is collected by interview, observation and documentation study which is then analyzed descriptively. The results showed that potential folklore on Pisang Island was about the prohibition of killing or flora and fauna (such as ketapang, rengas, stingrays, turtles, black eagles, owls, and large egrets), prohibition of activities in additional months, sacred tombs, and old wells. Indirectly, folklore contributes to supporting environment, because the community continues to approve the preservation of environment by accepting the myths that are still believed. Efforts to conserve the environment on small islands, such as Pisang Island, need to be done through the preservation of folklore that develops in the community. In addition, information boards related to the restrictions that are needed in the region need to be provided, so that tourists who visit more easily understand it.